Suicide, Self-Harm, & Traumatic Stress Exposure: A Trauma-Informed Approach to the Evaluation and Management of Suicide Risk. Issue 4 (1st October 2020) - Asarnow, Joan Rosenbaum; Goldston, David B.; Tunno, Angela M.; Inscoe, Adrienne Banny; Pynoos, Robert
ABSTRACT: Suicide and self-harm are major public health problems. Individuals who die by or attempt suicide and those who self-harm have elevated rates of traumatic stress exposure, underscoring the importance of a trauma-informed approach to suicide prevention. Rooted in the evidence on care for traumatic stress and suicide prevention, and our collective experience as clinicians and clinical researchers, this manuscript bridges these two literatures to offer clinical guidance on an evidence-based trauma-informed approach to suicide prevention. We describe our evidence-based approach to trauma-informed suicide prevention care: SAFETY-Acute (A) also known as the Family Intervention for Suicide Prevention (FISP). This approach offers a therapeutic assessment and intervention following a suicidal episode that aims to further assess safety and engage in a developmentally-informed safety planning process with the youth and parents/caregivers. In randomized controlled trials, SAFETY-A has demonstrated efficacy for improving continuity of care after an Emergency Department visit for suicidality (Objective 8.4 of the National Strategy for Suicide Prevention) and for reducing suicide attempt risk when combined with evidence-based follow-up treatment. We illustrate the approach with a case example, and offer comments based on our experience across diverse clinical settings including emergency and crisis services, outpatient clinics, and schools.